Laminaria japonica Aresch-Derived Fucoidan Ameliorates Hyperlipidemia by Upregulating LXRs and Suppressing SREBPs - Yan Zhang; Tian Liu; Ze-Jie Qu; Xue Wang; Wen-Gang Song; Shou-Dong Guo (Cardiovascular Therapeutics)
Cardiovascular disease (CVD) is the leading cause of morbidity and mortality worldwide, and hyperlipidemia is one major inducing factor of CVD. It is worthy to note that fucoidans are reported to have hypolipidemic activity with species specificity; however, the underlying mechanisms of action are far from clarification. This study is aimed at investigating the plasma lipid-lowering mechanisms of the fucoidan from L. japonica Aresch by detecting the levels of hepatic genes that are involved in lipid metabolism. Our results demonstrated that the fucoidan F3 significantly lowered total cholesterol and triglyceride in C57BL/6J mice fed a high-fat diet. In the mouse liver, fucoidan F3 intervention significantly increased the gene expression of peroxisome proliferator-activated receptor (PPAR) α, liver X receptor (LXR) α and β, and ATP-binding cassette transporter (ABC) G1 and G8 and decreased the expression of proprotein convertase subtilisin/kexin type 9 (PCSK9), low-density lipoprotein receptor, cholesterol 7 alpha-hydroxylase A1, and sterol regulatory element-binding protein (SREBP) 1c and SREBP-2. These results demonstrated that the antihyperlipidemic effects of fucoidan F3 are related to its activation of PPARα and LXR/ABC signaling pathways and inactivation of SREBPs. In conclusion, fucoidan F3 may be explored as a potential compound for prevention or treatment of lipid disorders.